Maternal Plasma 25-Hydroxyvitamin D during Gestation Is Positively Associated with Neurocognitive Development in Offspring at Age 4–6 Years. Issue 1 (2nd November 2020) - Melough, Melissa M; Murphy, Laura E; Graff, J Carolyn; Derefinko, Karen J; LeWinn, Kaja Z; Bush, Nicole R; Enquobahrie, Daniel A; Loftus, Christine T; Kocak, Mehmet; Sathyanarayana, Sheela; Tylavsky, Frances A
ABSTRACT: Background: Vitamin D is critical to embryonic neuronal differentiation and other developmental processes that may affect future neurocognitive function. However, observational studies have found inconsistent associations between gestational vitamin D and neurocognitive outcomes. Objectives: We examined the association of gestational 25-hydroxyvitamin D [25(OH)D] with children's IQ at 4–6 y, and explored whether associations differed by race. Methods: This study used data from the CANDLE (Conditions Affecting Neurocognitive Development and Learning in Early Childhood) cohort. Between 2006 and 2011, CANDLE recruited 1503 women in their second trimester of healthy singleton pregnancies. Inclusion criteria for this analysis were gestation of ≥34 wk and availability of 25(OH)D and IQ data. Associations between second-trimester 25(OH)D plasma concentration and Stanford-Binet IQ scores in offspring at 4–6 y were examined using multivariable linear regression; interaction terms were used to explore possible effect modification by race. Results: Mean ± SD 25(OH)D concentration among 1019 eligible dyads was 21.6 ± 8.4 ng/mL, measured at a mean ± SD gestational age of 23.0 ± 3.0 wk. Vitamin D deficiency [25(OH)D < 20 ng/mL] was observed in 45.6%. Maternal 25(OH)D differed by race with a mean ± SD of 19.8 ± 7.2 ng/mL in Blacks sand 25.9 ± 9.3 ng/mL in Whites ( P   < 0.001). In adjusted models a 10-ng/mL increase in 25(OH)D was associated with a 1.17-point higher Full Scale IQ (95% CI: 0.27, 2.06 points), a 1.17-point higher Verbal IQ (95% CI: 0.19, 2.15 points), and a 1.03-point higher Nonverbal IQ (95% CI: 0.10, 1.95 points). We observed no evidence of effect modification by race. Conclusions: Second-trimester maternal 25(OH)D was positively associated with IQ at 4–6 y, suggesting that gestational vitamin D status may be an important predictor of neurocognitive development. These findings may help inform prenatal nutrition recommendations and may be especially relevant for Black and other dark-skinned women at high risk of vitamin D deficiency.